(untitled) (Journal of the College of Education for Women, 2019)
Through his female characters, Walt Disney was able to reflect thedevelopment of the general outlook upon women in the Western world over a periodof sixty years.This paper sheds light in how the cartoon characters changed in their reactionto problems and means of solving them from the 30s through to the 90s of theprevious century. The main characters will be seen according to the films’ dates ofproduction and release.